Enhancing Listening Skills Through Communicative Language Teaching Using Technology Based Media in Elementary School - Siburian, Tria Joys; Sinaga, Yenni Adelina; Rajagukguk, Oktania; Herman, Herman; Sitanggang, Anita; Sitohang, Sukardo; Hasibuan, Nurainun (Jurnal Pengabdian Nusantara, 2026)
This community service program aimed to improve listening comprehension among fourth-grade students at SD Negeri 124385 Pematangsiantar through the integration of BBC Learning English audio and the Communicative Language Teaching (CLT) approach. The problem addressed was the limited use of authentic listening activities in classrooms. The program involved 19 students and was carried out in three phases: preparation, implementation, and evaluation. During the implementation, students participated in contextual listening tasks, vocabulary repetition, group analysis, and interactive question sessions. Rather than using formal tests, the evaluation focused on student engagement and response accuracy through observation. Results showed that 78.95% of students achieved strong listening performance. The findings suggest that integrating Communicative Language Teaching with accessible audio materials supports effective and affordable listening skill development in elementary classrooms.